Pelatihan Keterampilan Pengolahan Nugget Ikan Nila kepada Kader Posyandu Mekar Baru - Warsidah, Warsidah (Jurnal Indonesia Mengabdi, 2024)
One source of protein needed by the human body, especially during the growth and development period, is fish and its derivatives. Fish nuggets are a preparation made from sea fish or freshwater fish, which can practically be consumed as a side dish or snack. The aim of this community service activity (PKM) is to train Mekar Baru posyandu cadres in the skills of making tilapia nuggets. The activity was attended by 15 participants, including posyandu cadres at the Mekar Baru Village Community Health Center. The activity was carried out using educational lecture methods and practice in making nuggets made from tilapia fish. From the results of the evaluation of activities carried out using the questionnaire method at the beginning and end of the activity, it showed that there was an increase in the understanding and skills of Mekar Baru posyandu cadres in processing nuggets made from tilapia fish.